Physically active individuals look for more: An eye‐tracking study of attentional bias. (11th April 2020) - Cheval, Boris; Miller, Matthew W.; Orsholits, Dan; Berry, Tanya; Sander, David; Boisgontier, Matthieu P.
Abstract: Attentional capture by exercise‐related stimuli is important for the regulation of physical activity. Attentional processing underlying this capture has been investigated with indirect behavioral measures based on reaction times. To investigate more direct measures of visual spatial attention toward physical activity (vs. inactivity) stimuli, we used eye‐tracking and a visual dot probe task in 77 young adults with various level of physical activity. Reaction times to detect a dot appearing in the area previously occupied by a physical activity (vs. inactivity) stimulus were an indirect measure of attentional bias. The first picture gaze and viewing time were more direct measures of attentional orienting and attentional engagement, respectively. Pupil dilation was an indicator of arousal. Reaction times revealed a two‐way interaction between the location of the dot and participants' usual level of physical activity. Only participants with a high level of physical activity more quickly detected a dot when it appeared in the area previously occupied by a physical activity stimulus. Eye‐tracking results showed greater odds of first gazing at physical activity stimuli and for a longer time, and a greater decrease in pupil size when viewing physical activity stimuli when usual level of physical activity was moderate or high, but not low. The variance explained in the outcomes ranged from 13.9% (pupil dilation) to 40% (reaction times). Overall, as hypothesized, compared to less physically active participants, participants who were more physically active demonstrated indirect (reaction times) and direct (first gaze, viewing time) evidence of a more pronounced attentional bias toward physical activity. Physical activity stimuli biased attention, with a pronounced effect when the level of physical activity was higher. These findings suggest that physical activity stimuli are relevant to the current concerns of moderately and highly active individuals. Abstract : Behavioral studies based on reaction‐time tasks suggest that active individuals are attentionally biased toward physical activity. Here, based on eye‐tracking evidence, we show that moderately‐to‐highly active individuals orient their attention toward physical activity stimuli more often and for longer periods of time than toward physical inactivity stimuli. Interventions aiming to promote physical activity might benefit from testing the effectiveness of attentional bias modification treatments.